2016
DOI: 10.1111/1556-4029.13197
|View full text |Cite
|
Sign up to set email alerts
|

Fatal Clostridium perfringens Septicemia After Colonoscopic Polypectomy, Without Bowel Perforation

Abstract: Since its introduction, colonoscopy has played an important role as a diagnostic, therapeutic, and screening tool. In general, colonoscopy is regarded as a safe procedure, but complications may occur. The most dreaded of these complications is colonic perforation. Bacteremia postprocedure may occur, and although it is not uncommon, it rarely results in clinically significant complications. Patients with IBD (inflammatory bowel disease) are a high-risk population for bacteremia, which may leads to bowel wall ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…This study identified that pancreatic, small bowel, and splenic surgeries were associated with higher risks among patients aged 18-44, 45-64, and ≥65 years, respectively. In addition, there is much evidence claiming that postoperative sepsis was found in patients after an uncomplicated colonoscopic polypectomy, which is regarded as a safe procedure, due to unidentified abdominal infections [24,25]. These results suggest that general abdominal procedures, including not only complex surgeries but also routine procedures, pose a significant risk for the development of postoperative sepsis.…”
Section: Table 1 Continued: Basic Characteristics Of the Study Particmentioning
confidence: 99%
“…This study identified that pancreatic, small bowel, and splenic surgeries were associated with higher risks among patients aged 18-44, 45-64, and ≥65 years, respectively. In addition, there is much evidence claiming that postoperative sepsis was found in patients after an uncomplicated colonoscopic polypectomy, which is regarded as a safe procedure, due to unidentified abdominal infections [24,25]. These results suggest that general abdominal procedures, including not only complex surgeries but also routine procedures, pose a significant risk for the development of postoperative sepsis.…”
Section: Table 1 Continued: Basic Characteristics Of the Study Particmentioning
confidence: 99%
“…The pathophysiological events underlying sepsis have a strong impact on the function of each organ [ 1 , 3 , 7 ] since the organ failure induced gives rise, in most cases, to morphological alterations that can be evaluated both macroscopically and microscopically. We start by suggesting some works describing the main post-mortem macroscopic and histological changes ( Table 1 ) detected on septic organs [ 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…The most peculiar findings were associated to septic processes sustained by specific bacteria, such as those responsible for gas gangrene. An example is reported in a case report by Gioia et al [ 20 ], where the septic process sustained by Clostridium spp. caused retroperitoneum and thigh muscles gas gangrene and iliopsoas myonecrosis, along with palpable crepitation and haemorrhagic-oedematous adipose tissues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations